Execution Guarantee Fiduciary Consequence Debtor Default on Agreement Credit - Ismayani, Ismayani; Muhlizar, Muhlizar (Faculty of Law, Universitas Pekalongan, 2024)
The result of the reformulation of the ideal of legal certainty is that there is a conflict regarding the meaning of legal certainty between debtors and creditors. Based on the definition of legal certainty according to Utrecht, debtors and creditors in practice cannot yet understand the limits of permissible and prohibited acts and there is still legal insecurity which causes arbitrariness. Many debtors are still embezzling fiduciary collateral objects, while many creditors are also carrying out forced withdrawals of fiduciary collateral objects. This analysis method uses a qualitative approach, namely to analyze the data used for normative aspects with a descriptive analysis method, namely describing the data in as much detail as possible regarding individuals and other symptoms. The aim of this method is to obtain and provide an overview of the data that has been obtained and relate them to each other with the aim of obtaining the truth. The fiduciary guarantee deed at least contains information regarding the identity of the parties entering into the fiduciary guarantee agreement, including the day, date and time. making a deed, data on the main agreement that is guaranteed by fiduciary, a description of the building which includes identification of the building and an explanation of the proof of ownership, the value of the guarantee and the value of the object that is the object of the fiduciary guarantee (Article 6 of Law No. 42 of 1999 concerning Fiduciary Guarantees). Moving on from this phenomenon, the author is interested in discussing this problem with the topic of the problem: What legal violations occurred in the practice of executing fiduciary guarantee objects after the enactment of Law Number 42 of 1999 concerning Fiduciary Guarantees. If the object of the collateral is a movable object, it can be bound by a fiduciary agreement. The success or failure of this form of fiduciary guarantee depends solely on the bona fides and good faith of the debtor.